Educational Values in the Novel Jaša Dalmatin, the Viceroy of Gujarati by Ivana Brlić-Mažuranić - HULJEV, Antonija (Anafora, 2023)
Ivana Brlić-Mažuranić (1874 – 1938), a Croatian children and youth authoress, entered the Croatian literary canon quite a long time ago. However, one may talk about the reception of her works mostly on the level of the novel The Marvelous Adventures of Hlapić the Apprentice and the fairy tale collection Croatian Tales of Long Ago. When it comes to the novel Jaša Dalmatin, the Viceroy of Gujarati, there is an almost complete absence of literary and critical reception. This novel is comprised of two completed and one incomplete part (Conclusion), which encompasses the period from 1478 to 1509, and resembles more a sketch and a guideline for the completion of a future novel. For an understanding of the novel, the authoress’ addendum, A Short Glossary of Certain Jaša Dalmatin’s Terms, is also important, and may be understood as a sort of subtext. The Croat, Jaša Dalmatin, an Ottoman slave, is a builder and visionary who erects on the shores of the Indian Ocean an unconquerable fortification based upon his own childhood image of his hometown, Dubrovnik. The character of Jaša Dalmatin, as well as the novel overall, have become a desirable identification model and an educational orientation. The paper provides an analyis, a typology, and a hierarchy of the fundamental human and educational values pursuant to the divergence levels between modernity and the moral education in children’s literature.